Carbohydrate oral rinsing, cycling performance and individual complex carbohydrate taste sensitivity - Hartley, C.; Carr, A.; Roberts, S. S. H.; Bredie, W. L. P.; Keast, R. S. J. (Nutrients, 2024)
The aim of this pilot study was to determine the effect of individual complex carbohydrate taste sensitivity on cycling performance with complex carbohydrate oral rinsing. Ten male participants completed five cycling time trials in a fasted state with a seven-day washout period between each trial. Participants completed a fixed amount of work (738.45 ± 150.74 kJ) as fast as possible on a cycle ergometer while rinsing with an oral rinse for 10 s every 12.5% of the trial. An oral rinse (maltodextrin, oligofructose, glucose, sucralose or water control) was given per visit in a randomised, crossover, blinded design. Afterwards, participants had their taste assessed with three stimuli, complex carbohydrate (maltodextrin), sweet (glucose) and sour (citric acid), using taste assessment protocol to determine individual taste sensitivity status. Participants were subsequently grouped according to their complex carbohydrate taste sensitivity and complex carbohydrate taste intensity. There were no significant effects of the oral rinses on cycling performance time (p = 0.173). Participants who did not have improvements in exercise performance with the maltodextrin rinse experienced a stronger taste intensity with complex carbohydrate stimuli at baseline (p = 0.047) and overall (p = 0.047) than those who did have improvements in performance. Overall, a carbohydrate oral rinse was ineffective in significantly improving cycling performance in comparison with a water control. However, when participants were grouped according to complex carbohydrate taste intensity, differences in exercise performance suggest that individual sensitivity status to complex carbohydrates could impact the efficacy of a carbohydrate-based oral rinse.